Seeing as Practice - Schuermann, Eva. author. aut Link
XI, 209 p. 9 illus., 8 illus. in color.
Keywords: This study provides an overview of philosophical questions relating to sight and vision. It discusses the intertwinement of seeing and ways of seeing against the background of an entirely different theoretical framework. Seeing is both a proven means of acquiring information and a personality-specific way of disclosing the apparent, perceptible world, conditioned by individual and cultural variations. In a peculiar way, the eye holds a middle position between inside and outside of the self and its relations towards itself and others. This book provides a way out of false alternatives by offering a third way with reference to concrete cases of aesthetical and ethical experiences. It will be of particular interest to scholars of the phenomenology of sight and it will be valuable to students of philosophy, cultural studies and art.